2019
DOI: 10.4236/pp.2019.102007
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic, Antimicrobial and Antioxidant Properties of <i>Commelina diffusa</i> Burm. F.

Abstract: Commelina diffusa Burm. F. is a herbaceous tropical plant with different traditional medicinal uses. Present study is aimed to isolate the bioactive compounds from DCM-Methanol extract of the powdered whole plant of Commelina diffusa and to investigate the cytotoxic, antimicrobial and antioxidant activities of the crude extract and its twelve vacuum liquid chromatographic fraction (CD 1-12 ). Vacuum Liquid Chromatography (VLC) was employed to isolate bioactive metabolites. The physicochemical properties of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Some previous phytochemical studies show the presence of glycoside, flavonoid, sterol, terpenoids, tannin, alkaloid and anthraquinones in C. diffusa (Nasrin et al 2019). According to the work of Okoronkwo et al (2015), A. ciliata is rich in several chemical groups such as alkaloids, tannins, saponins and mineral compounds namely calcium, magnesium, iron, phosphorus and sodium.…”
Section: Introductionmentioning
confidence: 98%
“…Some previous phytochemical studies show the presence of glycoside, flavonoid, sterol, terpenoids, tannin, alkaloid and anthraquinones in C. diffusa (Nasrin et al 2019). According to the work of Okoronkwo et al (2015), A. ciliata is rich in several chemical groups such as alkaloids, tannins, saponins and mineral compounds namely calcium, magnesium, iron, phosphorus and sodium.…”
Section: Introductionmentioning
confidence: 98%
“…The plant also showed positive hepato-protective and nephro-protective activities in leaf extract treated rats. 13,14 Sultana et al also reported CNS depressant activity of methanolic extract of C. diffusa. 15 The antimicrobial activity of the plant was also established with a strong positive result.…”
Section: Introductionmentioning
confidence: 98%
“…F. (Day flower, Bengali name: manaina), a medicinal herb is used to treat various diseases traditionally. Biological activity evaluation revealed its potential in anti-inflammatory, 4 antioxidant, 3,4 antibacterial, 3,5 anti-fungal, 5 nephroprotective, 6 hepatoprotective, 6 CNS depressant 7 activities of this plant. The main objective of the present study was to isolate and characterize the endophytic fungi of C. diffusa available in Bangladesh and evaluation of their antibacterial, antioxidant and cytotoxicity activities.…”
Section: Introductionmentioning
confidence: 98%
“…F. has been investigated in this study. 3 Commelina diffusa Burm. F. (Day flower, Bengali name: manaina), a medicinal herb is used to treat various diseases traditionally.…”
Section: Introductionmentioning
confidence: 99%